The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/15578771.2020.1730527
|View full text |Cite
|
Sign up to set email alerts
|

Electronic (e-) Procurement Adoption and Users’ Experience in the Nigerian Construction Sector

Abstract: The adoption of e-Procurement in construction is gaining global acceptability, but in a developing country like Nigeria, there is a paucity of studies on the e-Procurement tools/applications used by construction industry stakeholders and their experiences with this technology. This study investigated e-Procurement adoption and users' experience with it in the Nigerian construction industry using a questionnaire survey of 759 users of e-Procurement. The data were analyzed using descriptive statistics and factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Other relevant studies on EP adoption regarding significant issues such as the user experiences on EP platforms and supplier's perspectives have been conducted by [57,[81][82][83]. For instance, inferring from the study of [84,85] the two end-to-end spectrums of e-procurement adoption encapsulates initial adoption (microscale) and institutionalization (macroscale).…”
Section: Ep Adoption Models and Associated Success Factorsmentioning
confidence: 99%
“…Other relevant studies on EP adoption regarding significant issues such as the user experiences on EP platforms and supplier's perspectives have been conducted by [57,[81][82][83]. For instance, inferring from the study of [84,85] the two end-to-end spectrums of e-procurement adoption encapsulates initial adoption (microscale) and institutionalization (macroscale).…”
Section: Ep Adoption Models and Associated Success Factorsmentioning
confidence: 99%
“…User satisfaction is important to determine the success of an e-procurement system [9]. Similarly, Ibem et al [17] mentioned that users' experience with e-procurement is influenced by the ease of use of the technology. [3] reiterates that when procurements become increasingly complex, local governments are less likely to rely on the technology support associated with e-procurement.…”
Section: "System Has Privacy and Security With Password Protection" (...mentioning
confidence: 99%
“…Despite the fact that e-procurement technology is now compulsory in many organizations or industries, individual acceptance is sometimes difficult to force, and disgruntled users will find ways to avoid using the system. Although there is a lack of published articles on users' experience with eprocurement that the authors have identified, it can be concluded from the existing studies that users' experience with e-procurement from various perspectives by companies is still insufficient [17]. In the work by Deraman et al [18], it is mentioned that e-procurement is one of the initiatives by the government to meet enterprise objectives, but they fail to generate quantifiable benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of E-procurement is brought so many changes in the business (Aberdeen, 2001). In the research relevant data have been gathered about the factors that affect the Supply chain performance and gaps are identified which filled by accepting all the e-invoicing and e-payments factors and elements that are important in making effective supply chain performance so, there is a gap found in which a cross level analysis is not investigated accordingly, which have a most worthy of investigation while considering the importance their encouragement of characteristics and technology usage, in this study the main focus is on the reducing the cost, purchasing cycle process and reduce the risk of payments through e-procurement which is the main factor which reduce the both internal and external risk (Ibem, 2020).…”
Section: Significance Of the Researchmentioning
confidence: 99%